Physiological responses and perceived exertion during international taekwondo competition - Bridge, C. A.; Jones, M. A.; Drust, B. (International Journal of Sports Physiology and Performance, 2009)
Purpose: To investigate the physiological responses and perceived exertion during international Taekwondo competition. Methods: Eight male Taekwondo black belts (mean ± SD, age 22 ± 4 y, body mass 69.4 ± 13.4 kg, height 1.82 ± 0.10 m, competition experience 9 ± 5 y) took part in an international-level Taekwondo competition. Each combat included three 2-min rounds with 30 s of recovery between each round. Heart rate (HR) was recorded at 5-s intervals during each combat. Capillary blood lactate samples were taken from the fingertip 1 min before competition, directly after each round and 1 min after competition. Competitors` rating of perceived exertion (RPE) was recorded for each round using Borg`s 6-to-20 scale. Results: HR (round 1: 175 ± 15 to round 3: 187 ± 8 beats/min; P < .05), percentage of HR maximum (round 1: 89 ± 8 to round 3: 96 ± 5% HRmax; P < .05), blood lactate (round 1: 7.5 ± 1.6 to round 3: 11.9 ± 2.1 mmol/L; P < .05) and RPE (round 1: 11 ± 2 to round 3: 14 ± 2; P < .05; mean ± SD) increased significantly across rounds. Conclusions: International-level Taekwondo competition elicited near-maximal cardiovascular responses, high blood lactate concentrations, and increases in competitors` RPE across combat. Training should therefore include exercise bouts that sufficiently stimulate both aerobic and anaerobic metabolism.